Produção de mudas de espécies florestais em sistema hidropônico e convencional - Farias, Elias de Sá (2017)
Modern forestry is a continuous evolving science and is always incorporating new techniques and methodologies aimed at the efficient implantation of forests and increase in productivity, in this context a modified hydroponic system has shown to be promising to obtain seedlings of agronomic, fruit and forest species. The objective of this work was to analyze the effect of two different systems of seedling production: hydroponic and conventional, being tested in each system three plastic tube sizes (for seedlings), comparing the two different systems regarding the quality of the seedlings obtained and verify the viability of the implantation of these seedlings in the field. Simultaneous experiments were carried out with seven forest species in hydroponic and conventional conditions, and data on growth, biomass and physiological variables were analyzed. The analyzes consisted of tests of average for the different sizes of tubes for each species as a function of the production system and also the joint analysis was carried out to compare the systems. Taking into account the experimental conditions, the hydroponic system allowed to obtain quality seedlings for acrocarpo (Acrocarpus fraxinifolius), cedro (Cedrella fissilis), paricá (Schizolobium amazonicum) and pau-pereira (Platycyamus regnellii) in only 60 days after implantation in the system. The forest species: garapa (Apuleia leiocarpa), jacarandá-branco (Platypodium elegans) and sucupira (Bowdichia virgilioides) did not adapt to the conditions of cultivation of the hydroponic system used. The best plastic tube size for the production of seedlings varied according to the production system and the species, being in the hydroponic system: 280 cm³ for acrocarpo and pau-pereira; 180 cm³ for cedro and paricá; And in the conventional system: 280 cm³ tube for cedro, jacarandá-branco, paricá and pau-pereira; and 180 cm³ tube for acrocarpo and garapa. The morphological variables were efficient in the evaluation of the growth and performance of the seedlings, while the physiological variables obtained by the estimation of infrared gas exchanges presented little power of distinction between the treatments. The seedlings produced in the hydroponic system were successfully implanted in the field, with mortality rates similar to those of the conventional system and higher growth rates. The cut of the external roots to the tube compromised the growth of acrocarpo seedlings from the modified hydroponic system. The other species were indifferent to this practice.